Diagnostic and interventional actions in the teaching and learning process in the food trade (Research, Society and Development, 2022)
Objective: Describe the impact of guidance and analysis as in-service education and instruction tools. Methods: This is an exploratory qualitative and quantitative in a work environment (restaurant) in the city of Petrolina/PE. Two technical visits were carried out, in the first a checklist was applied to evaluate good food handling practices, the collection of samples of food, water and surfaces for microbiological analysis. After interpreting the results, an action plan was built and delivered, pointing out non-conformities and suggesting corrective actions, as well as online training. On the second visit, the establishment was reassessed and new microbiological analyzes performed. Results: It was found on the first visit that the establishment was 86.14% adequate, for hygienic-sanitary conditions, and contamination by S. aureus (4.8 x 10² CFU/cm²) was evidenced in the sample of sliced ​​meat, but not on a skewer. In the second visit, the adequacy increased (91.48%) items related to control actions, but there was contamination of both meat samples on the second visit (7.0 x 10³ CFU/g, and 3 x 10² CFU/g) . Conclusion: In-service education is an effective method for food handlers, but it does not exclude the need for continuous and specialized supervision.